Cultural Values in Bengkulu Folk Tales: An Analysis of Folk Stories from Bengkulu 2 by Naim Emel Prahana - Fridiawan Surya Kencana (Yayasan Darussalam Bengkulu, 2024)
Folklore functions as a vital medium for preserving cultural identity and transmitting moral values, yet Bengkulu folktales remain underexplored in academic research compared to other regional traditions in Indonesia. This study aimed to analyze the cultural values contained in Cerita Rakyat dari Bengkulu 2 by Naim Emel Prahana to classify and interpret the moral and social wisdom embedded within the narratives. A qualitative descriptive method was employed, with data collected through documentation of selected folktales and analyzed using content analysis to identify recurring themes. The analysis focused on four relational domains: human–God, human–nature, human–human, and human–self. The findings revealed that the folktales convey religious devotion, ecological awareness, social solidarity, and personal integrity, demonstrating that local wisdom is deeply interwoven into narrative structures. These results indicate that folklore in Bengkulu not only entertains but also educates and preserves community identity by transmitting values across generations. The novelty of this research lies in its systematic categorization of cultural values within Bengkulu folktales, an area seldom addressed in prior literature. The implications suggest that integrating regional folklore into educational curricula can enhance cultural literacy, strengthen character education, and support the safeguarding of Indonesia’s intangible cultural heritage, while future studies should adopt broader ethnographic approaches to capture folklore in its living context.